2021
DOI: 10.1108/ijhrh-03-2021-0064
|View full text |Cite
|
Sign up to set email alerts
|

Work environment and performance among nurses: a significant way to overcome violation of human rights in the health sector

Abstract: Purpose The study aims to purpose the role of the work environment (WE) towards employees’ performance (EP) in Pakistan’s health sector. Design/methodology/approach Data-wise, the study is cross-sectional and random sampling was used to glean the response from the trained health nurses in Pakistan. The survey questionnaire was used as a primary tool to collect the data. In total, 306 usable samples as used to infer the final consequences. Findings The structural equation modeling through AMOS 26.0 for wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 108 publications
(134 reference statements)
0
9
0
Order By: Relevance
“…, 2013; Shahzad, 2014; Bhatti et al. , 2021a, b). On the other hand, EP is reduced significantly by stress, role doubt, role conflict, lack of feedback, overloading, role ambiguity, psychological strain, work overload and lack of peer support and training (Bashir and Ramay, 2010; Dar et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2013; Shahzad, 2014; Bhatti et al. , 2021a, b). On the other hand, EP is reduced significantly by stress, role doubt, role conflict, lack of feedback, overloading, role ambiguity, psychological strain, work overload and lack of peer support and training (Bashir and Ramay, 2010; Dar et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, employee evaluation of salary, promotion opportunities, recognition, job design, quality of organizational communication, and workplace spirituality all play a role in determining employee motivation to lead (Porter et al, 2016). The work environment consists of: the physical environment is defined as an environment that can be seen in real terms and with the naked eye, such as: lighting, room layout, room design and color, and so on, while the non-physical environment is defined as an environment that is invisible, but can be felt in its shape, such as : support from superiors, good communication between superiors or with coworkers, perceived justice in the workplace both directly and indirectly financially, and so on (Bhatti et al, 2021). Evidenced by several previous studies that examine the relationship between the work environment and motivation, namely (Rulianti et al, 2021;Asfar & Anggraeni, 2020;Wiryawan et al, 2020;Kultsum, 2017;Josephine, 2017) found that the work environment can increase motivation employees in carrying out their duties.…”
Section: Work Environment and Motivationmentioning
confidence: 99%
“…Employee morale can be built by a good work environment (Santika & Antari, 2020), where a good environment will lead to motivation and ultimately will increase employee morale to perform better in completing each job (Nugroho et al, 2020). A good working environment allows employees to be more productive, because there is a spirit within them to continue to play an active role in completing their tasks (Bhatti et al, 2021). Likewise, research developed by (Basori et al, 2017;Josephine, 2017) found that the work environment can improve employee performance through the role of motivation.…”
Section: Work Environment Positively Affects Work Morale Mediated By ...mentioning
confidence: 99%
“…It also creates a direct link between the victim and the violator and states that International law not only governs the behavior of states but also encompasses non-state actors and private individuals. Moreover the local authorities too have completely failed in providing proper means and channels of addressing such a heinous crime existent in the society (Bhatti et al, 2021). Such failed legislation has further put a full stop on creating deterrence for all abusers because the punitive measure are not enough, nor do they suf􀅫ice in limiting violence against women in all ambits.…”
Section: The Claimmentioning
confidence: 99%
“…State actors such as social workers, hospitals and police play a vital role in this regard. The reporting process of these non-governmental organizations, quash the notion of lack of knowledge which states maintain (Bhatti et al, 2021). The failure of legal systems to punish the perpetrators or provide redress to the victims, as a result of this it creates a major diversion between victims of systematic intimate violence from law, and law from victims of systematic intimate violence.…”
Section: International Obligation Of Statesmentioning
confidence: 99%